A veil in the oral cavity: report of two cases of oral synechiae. Issue 3 (March 2017) - Dongol, A.; Acharya, P.; Prasad, J.N.; Jaisani, M.R.
Abstract: An oral synechia is an adhesion between the maxilla and the mandible; these adhesions can be found at various locations in the oral cavity. The presence of oral synechiae associated with cleft palate represents a rare congenital deformity. Oral synechiae with cleft palate can have serious implications for airway management and feeding in babies, and hence requires early intervention to reduce morbidity. Two cases of congenital oral synechiae accompanied by cleft palate, in which the synechiae veiled the oral cavity restricting a detailed intraoral examination, are reported here.